Pengaruh Pendapatan, Pendidikan dan Jenis Kelamin Terhadap Literasi Keuangan Pada UMKM di Kecamatan Mengkendek - Selmi Lora Batara; Jemi Pabisangan Tahirs; Rati Pundissing (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The Influence of Level of Income, Education, and Gender on Financial Literacy in MSMEs in Mengkendek District"This study aims to determine the factors that influence the level of income, education and gender of MSMEs in the Mengkedek District. This type of research is quantitative research. The population in this study were 59 MSMEs owners in the Mengkendek District. The research sample was obtained from the calculation of the Slovin formula so that a total of 51 samples were obtained. This study uses primary data and secondary data obtained from the distribution of questionnaires and documentation. Data analysis techniques in this study were validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination and hypothesis testing.The results of this study indicate that the variables Income, Education and Gender together have a significant effect on Financial Literacy in MSMEs in the Mengkendek District.Â